Human Resource Preparation in Sharia-Inn at Malang City (Case Study Multi Sites Hotel Syariah 99 by VRV and Aurila Homestay Syariah) - Iklil Abdul Hamid Zuhri; Budi Eko Soetjipto; Ely Siswanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
In 2019 Indonesia was chosen as the world's best halal tourism in the world, so the government made the development of halal tourism is a priority program. Sharia-inn have the highest points in the assessment of halal tourism. Sharia-inn is basically not much different from conventional or non-sharia inn, but sharia-inn does not only provide overnight services. Sharia-inn also offers services and benefits that are more than just lodging in general, such as the provision of worship facilities, the presence of the holy Quran in each room, and the atmosphere of Islamic cultures that are applied to provide a more Islamic circumstance. This paper discusses the human resource preparation of sharia inn in Malang, precisely at Hotel Syariah 99 by VRV and Aurila Homestay Syariah, mainly examining the recruitment, selection, and training processes. By conducting interviews, observations, and documentation, this paper shows that the preparation of human resources in sharia inn is not much different from the preparation of human resources in conventional inns. The difference found in the human resource preparation process is only in the employee selection process in the form of a requirement that prospective applicants must be Muslim. Furthermore, in training activities that provide insight into Islamic culture adopted by sharia inn.